2009
DOI: 10.1016/j.cell.2009.04.060
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin1/ErbB4 Signaling Induces Cardiomyocyte Proliferation and Repair of Heart Injury

Abstract: Many organs rely on undifferentiated stem and progenitor cells for tissue regeneration. Whether differentiated cells themselves can contribute to cell replacement and tissue regeneration is a controversial question. Here, we show that differentiated heart muscle cells, cardiomyocytes, can be induced to proliferate and regenerate. We identify an underlying molecular mechanism for controlling this process that involves the growth factor neuregulin1 (NRG1) and its tyrosine kinase receptor, ErbB4. NRG1 induces mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
824
3
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 898 publications
(910 citation statements)
references
References 33 publications
46
824
3
10
Order By: Relevance
“…Analysis of isolated cardiomyocytes showed that M-phase cardiomyocytes were predominantly mononucleated (P < 0.001), which is in agreement with previous reports of cycling mononucleated cardiomyocytes in growing cats (19), rats (20), and mice (21).…”
Section: Resultssupporting
confidence: 91%
“…Analysis of isolated cardiomyocytes showed that M-phase cardiomyocytes were predominantly mononucleated (P < 0.001), which is in agreement with previous reports of cycling mononucleated cardiomyocytes in growing cats (19), rats (20), and mice (21).…”
Section: Resultssupporting
confidence: 91%
“…Instead, we observed that the effect of both cytokines combined was lower than either alone. Thus, as both proteins may utilize similar signaling pathways [15,17], it is possible that they compete, limiting their combined effect. Indeed, this important observation should be considered when designing new studies involving combination therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to mediators of angiogenesis, the list of potential therapeutics for cardiac regeneration has continued to grow, and the use of factors involved in cardiac development, stem cell homing, cardiac differentiation/proliferation, or direct cardioprotection could lead to novel approaches for repairing damaged heart (reviewed in [4]). In this regard, in vitro studies have shown that adult cardiomyocytes do not proliferate under resting conditions, but may divide in response to extracellular mitogens, such as periostin [15], acidic fibroblast growth factor (FGF1) [16], and neuregulin-1 (NRG1) [17]. These findings have supported a new paradigm, which suggests that the heart might be capable of repair and regrowth in response to extracellular mitogens.…”
Section: Introductionmentioning
confidence: 98%
“…Studies have demonstrated that in addition to doxorubicin-induced heart failure, Neuregulin1 also improves cardiac function in ischemiareperfusion, viral infection, and pacing induced heart failure (Liu et al, 2006;Bersell et al, 2009;Hedhli et al, 2011). In addition, Neuregulin1 promotes cell cycle reentry of differentiated adult cardiomyocytes, improves angiogenesis in the heart (Bersell et al, 2009;Hedhli et al, 2011), and promotes embryonic stem cell differentiation into the cardiac lineage (Sun et al, 2011). Clinical trials are ongoing using Neureuglin1 for the treatment of heart failure in patients (Gao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%